MODEL KEMITRAAN DALAM POLA PEMBIAYAAN PERKEBUNAN SAWIT - Zamzami, Zamzami (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2011)
Palm plantations is one of the relatively advanced plantations in Indonesia. One of the most developed model of partnership is the PIR-Bun. Where large companies as a nucleus and Farmers as plasma. With the relative number of the application of the PIR-Bun, the more rapid development of oil palm plantations.